Chitosan-bionic MOFs adsorbent as well as preparation method and application thereof

By using chitosan-bionic MOFs adsorbent, the problems of low efficiency and low selectivity of seawater uranium extraction technology are solved, and efficient and environmentally friendly seawater uranium extraction effect is achieved.

CN119608123APending Publication Date: 2025-03-14HENAN UNIV OF URBAN CONSTR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411900679.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing seawater uranium extraction technology is inefficient and low selectivity, resulting in high extraction costs and great environmental impact.

Method used

Adsorbents with high uranium selective adsorption properties and water stability are prepared by specific preparation methods, and they are applied to the adsorption process of uranium in seawater.

Benefits of technology

Efficient and environmentally friendly seawater uranium extraction is achieved, the adsorbent has a high distribution coefficient (Kd) of uranium, the adsorption amount reaches 790 mg/g, and the adsorption rate of more than 93% is maintained during the cycle test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608123A_ABST
    Figure CN119608123A_ABST
Patent Text Reader

Abstract

The invention discloses a chitosan-bionic MOFs adsorbent as well as a preparation method and application thereof, and relates to the technical field of uranium extraction from seawater. The preparation method comprises the following steps: putting ellagic acid into a container, adding copper nitrate, water, glacial acetic acid and DMF (Dimethyl Formamide), stirring and heating, cooling to room temperature, adding chitosan, stirring at room temperature, and centrifuging to obtain a solid, namely the chitosan-bionic MOFs adsorbent. The adsorbent has high selective adsorption performance on uranium, has high stability in water and can be used for extracting uranium from seawater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of uranium extraction from seawater, and in particular to a chitosan-bionic MOFs adsorbent and a preparation method and application thereof. Background Art

[0002] Against the backdrop of growing global energy demand, the importance of nuclear energy as a clean energy source has become increasingly prominent. However, the limited terrestrial uranium resources and the increasing difficulty of mining have made it particularly urgent to find new uranium resources. Traditional uranium mining is not only costly, but also causes serious damage to the environment, including surface damage, water and soil pollution, etc.

[0003] The waste and wastewater produced during uranium mining and smelting contain radioactive substances, posing a threat to the environment and human health. Therefore, developing new uranium extraction technologies and reducing environmental pollution have become important research directions in the field of nuclear energy.

[0004] The reserves of uranium in seawater are huge, totaling about 4.5 billion tons, but due to its extremely low concentration, extracting uranium from seawater faces huge challenges. In recent years, seawater uranium extraction technology has made some progress, but the existing technology still has problems of low efficiency and low selectivity, resulting in high extraction costs and the impact on the environment cannot be ignored. Summary of the invention

[0005] One of the purposes of the present invention is to provide a method for preparing a chitosan-biomimetic MOFs adsorbent, wherein the prepared adsorbent has a high selective adsorption performance for uranium and has strong stability in water.

[0006] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing a chitosan-bionic MOFs adsorbent comprises the following steps:

[0007] Take an appropriate amount of ellagic acid (EA) and put it into a container. Add an appropriate amount of copper nitrate, water, glacial acetic acid and DMF (N,N-dimethylformamide). After stirring and heating, cool to room temperature. Then add an appropriate amount of chitosan (CS for short), stir at room temperature, and centrifuge to obtain a solid, which is the chitosan-bionic MOFs adsorbent (CEM).

[0008] Furthermore, the mass ratio of ellagic acid, copper nitrate and chitosan is 6:3:10. For example, ellagic acid is 0.3 g, copper nitrate is 0.15 g, and chitosan is 0.5 g.

[0009] Further, every 0.3 g of ellagic acid corresponds to 0.15 g of copper nitrate, 5 mL of water, 7.5 mL of glacial acetic acid, 10 mL of DMF and 0.5 g of chitosan. For example, ellagic acid is 0.3 g, copper nitrate is 0.15 g, water is 5 mL, glacial acetic acid is 7.5 mL, DMF is 10 mL, and chitosan is 0.5 g.

[0010] Furthermore, the stirring and heating temperature is 120° C. and the time is 1 h.

[0011] Furthermore, the stirring time at room temperature is 0.5 h.

[0012] Furthermore, the centrifugal speed is 6000 r / min and the time is 5 min.

[0013] Furthermore, after the solid is obtained by centrifugation, it is dried at a drying temperature of 80°C.

[0014] Wherein, the water involved in the above preparation method may be deionized water, and the container involved in the above preparation method may be a beaker.

[0015] Another object of the present invention is to provide a chitosan-biomimetic MOFs adsorbent, which is prepared by the above-mentioned preparation method and can be used as an adsorbent for extracting uranium from seawater.

[0016] In addition, the chitosan-bionic MOFs adsorbent can be used in extracting uranium from seawater. Specifically, the chitosan-bionic MOFs adsorbent is added to seawater to adsorb uranium in the seawater.

[0017] Further, every 10 to 20 mg of chitosan-bionic MOFs adsorbent corresponds to 90 to 200 mL of seawater. Preferably, every 10 mg of chitosan-bionic MOFs adsorbent corresponds to 90 mL of seawater, or, every 20 mg of chitosan-bionic MOFs adsorbent corresponds to 200 mL of seawater. For example, the seawater is 90 mL, and the chitosan-bionic MOFs adsorbent is 10 mg; the seawater is 200 mL, and the chitosan-bionic MOFs adsorbent is 20 mg.

[0018] Furthermore, the pH of the seawater is 6-8 (for example, pH=6, 7, 8, preferably pH=6), and the temperature is 288-308K (for example, 288K, 298K, 308K, preferably 308K).

[0019] The present invention prepares a new type of material-chitosan / ellagic acid chitosan / ellagic acid copper-MOFs, namely chitosan-biomimetic MOFs adsorbent (CEM), which can be used as an adsorbent for uranium extraction from seawater. Experimental results show that CEM has high adsorption selectivity for uranium, and its distribution coefficient (Kd) for uranium is high, showing good adsorption performance. Under the temperature condition of 308K, the adsorption amount of uranium by CEM is as high as 790mg / g, which is outstanding in the current field of uranium extraction from seawater. After 7 consecutive adsorption-desorption cycle tests, CEM can still maintain a high adsorption rate of more than 93%, proving its excellent cycle stability and long-term application potential. The adsorption process of uranium by CEM is a spontaneous endothermic reaction, which means that in the natural environment, CEM can effectively extract uranium from seawater without additional energy input. In addition, the hydroxyl, amino and carboxyl groups on the surface of CEM all play an important role in the process of adsorbing uranium, and the presence of these active groups enhances the adsorption capacity of CEM for uranium. Therefore, the preparation and application of CEM provides a new method for extracting uranium from seawater with high efficiency and environmental protection. By using CEM, the shortage of uranium resources on land can be effectively alleviated, and the environmental pollution caused by traditional uranium mining and smelting can be significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 In the figure: (a) (including a1 and a2) is the scanning electron microscope (SEM) image of EM; (b) (including b1 and b2) is the scanning electron microscope (SEM) image of CEM; (c) is the Fourier transform infrared spectrum (FT-IR) spectrum of EM and CEM; (d) is the XRD spectrum of EM and CEM.

[0021] Figure 2 Thermogravimetric (TG) graphs of EM and CEM, where (a) is the thermogravimetric analysis (TG) curve of EM, and (b) is the thermogravimetric analysis (TG) curve of CEM.

[0022] Figure 3 Schematic diagram of the stability of CEM and EM in water, where (a) is natural seawater and (b) is 10 mg / L uranium solution.

[0023] Figure 4 Middle: (a) is a schematic diagram of the effect of initial pH value on CEM adsorption of uranium (298K, m=10mg, V=90mL, C0=10mg / L); (b) is a schematic diagram of the adsorption-desorption cycle of uranium by CEM.

[0024] Figure 5 Schematic diagram of the effect of adsorption time on the adsorption of U(VI) by CEM and EM, where (a) is fitted using the pseudo-first-order kinetic model and the pseudo-second-order kinetic model, and (b) is fitted using the intra-particle diffusion model.

[0025] Figure 6 Schematic diagram of the isotherm of uranium adsorption by CEM (pH=6, m=10 mg, V=90 mL), where (a) is before fitting, (b) is fitted using the Langmuir model, (c) is fitted using the Freundlich model, and (d) is fitted using the Langmuir-Freundlich model.

[0026] Figure 7 In the figure: (a) (including a1 and a2) is a schematic diagram of the selective adsorption performance of CEM and EM for uranium in simulated seawater; (b) and (c) are schematic diagrams of the effect of anions on the adsorption of uranium by CEM, where (b) is chloride ion (Cl - ), (c) is nitrate ion (NO3 - ).

[0027] Figure 8 In the figure: (a) (including a1 and a2) is a scanning electron microscope (SEM) image of CEM (CEM-U) after uranium adsorption; (b) (including b1 and b2) is a scanning electron microscope (SEM) image of CEM (D-CEM) after elution; (c) (including c1 to c8) is a scanning electron microscope (SEM) image of CEM (CEM-U - )’s SEM-Mapping image.

[0028] Fig. 9 These are scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) images of CEM, where (a) is CEM, (b) is CEM after uranium adsorption (CEM-U), and (c) is CEM after elution (D-CEM); (d) is the Fourier transform infrared spectroscopy (FT-IR) spectra of CEM-U, CEM-100U and D-CEM.

[0029] Fig.10 Schematic diagram of X-ray photoelectron spectroscopy (XPS) analysis of CEM before and after uranium adsorption (i.e., CEM and CEM-U). DETAILED DESCRIPTION

[0030] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with the examples, and the contents mentioned in the examples are not limitations of the present invention. It should be noted in advance that the following examples were completed in the laboratory, and those skilled in the art should understand that the amounts of the components given in the examples only represent the ratio relationship between the components, rather than specific limitations.

[0031] In order to alleviate the pressure of shortage of uranium resources on land and reduce the environmental pollution caused by uranium mining and smelting, this example uses chitosan, ellagic acid and copper nitrate as raw materials to prepare chitosan / ellagic acid chitosan / ellagic acid copper-MOFs (CEM) for uranium extraction from seawater, as follows.

[0032] 1. Preparation of chitosan-biomimetic MOFs adsorbent (CEM)

[0033] 1.1 Experimental Materials

[0034] Ellagic acid (EA) (C 14 H6O8, PubChem CID: 5281855, 98%), Chitosan (CS) (PubChem CID: 71853, degree of deacetylation≥95%, viscosity=100–200mpa.s), copper nitrate (Cu(NO3)2, PubChem CID: 15303652).

[0035] 1.2 Preparation of adsorbent

[0036] 1.2.1 Preparation of CEM

[0037] Take 0.3g of ellagic acid in a 100mL beaker, add 0.15g of copper nitrate, 5mL of deionized water, 7.5mL of glacial acetic acid and 10mL of DMF (N,N-dimethylformamide), stir and heat in a 120℃ oil bath for 1h, then let it cool to room temperature. Add 0.5g of chitosan, stir at room temperature for 0.5h, centrifuge at 6000r / min for 5min, and dry the obtained solid at 80℃ to obtain CEM.

[0038] 1.2.2 Preparation of EM

[0039] Take 0.3g of ellagic acid in a 100mL beaker, add 0.15g of copper nitrate, 5mL of deionized water, 7.5mL of glacial acetic acid and 10mL of DMF (N,N-dimethylformamide), stir and heat in a 120℃ oil bath for 1h, then let it cool to room temperature. Centrifuge at 6000r / min for 5min, and dry the obtained solid at 80℃ to obtain EM.

[0040] Among them, EM adsorbent is mainly used as a reference sample for comparison with CEM adsorbent.

[0041] 2. Related tests

[0042] 2.1 Adsorption experiment

[0043] Take 0-45 mg CEM at 25°C, adsorb 90 mL uranyl carbonate solution with a pH of 4-9 and a concentration of 10 mg / L, and adsorb with 0.1 M NaCO3 and 0.1 M HNO3 in a shaker for 12 h (175 r / min). After adsorption, take the supernatant and determine the uranium concentration in the solution by ICP and spectrophotometry. The adsorption rate of CEM to uranium (R) is calculated using formulas (1) and (2) respectively. α , %) and adsorption capacity (q e ,mg / g).

[0044]

[0045] Among them, C0 (mg / L) and C e (mg / L) represent the concentrations at initial adsorption and equilibrium adsorption, respectively. V(L) represents the volume of the mixture, and m(g) represents the mass of the adsorbent.

[0046] 2.2 Adsorption kinetics

[0047] At 25°C, 10 mg CEM was used to adsorb 90 mL of 5 mg / L and 10 mg / L uranyl carbonate solutions at pH = 6, respectively, and adsorbed on a shaker for 0-12 h (175 r / min). At the same time, 10 mg EM was used to adsorb 90 mL of 10 mg / L uranyl carbonate solution at pH = 6, and its adsorption kinetics was studied.

[0048] 2.3 Adsorption isotherms and adsorption thermodynamics

[0049] At 15°C (288K), 25°C (298K) and 35°C (308K), 10 mg CEM was used to adsorb 90 mL of uranyl carbonate solution with a concentration of 10-300 mg / L at pH = 6, and the Langmuir, Freundlich and Langmuir-Freundlich models were used for fitting and calculation.

[0050] 2.4 Adsorption selectivity

[0051] In order to study the adsorption selectivity of CEM for uranium, simulated seawater with a pH of 8 was prepared. At 25°C, 10 mg CEM was used for adsorption. The concentrations of each ion in the solution before and after adsorption were measured, and the Kd value was calculated.

[0052] In order to study the effect of anions on the adsorption of uranium by CEM, the NO3 - (0.001-0.015mol / L) and Cl - (0.1-0.8 mol / L) pH=6, 10 mg / L uranyl carbonate solution was adsorbed with 10 mg CEM, and the uranium concentration in the solution before and after adsorption was measured.

[0053] 2.5 Adsorbent recycling

[0054] 200 mL of 5 mg / L uranium solution was adsorbed with 20 mg CEM. After adsorption, 25 mL of 1 M sodium chloride + 3 g / L sodium carbonate was used to desorb the adsorbent at 40 ° C. The uranium concentration in the solution before and after adsorption and after desorption was measured.

[0055] 2.6 Characterization

[0056] In order to study the adsorption mechanism of uranium on CEM, SEM, FT-IR, XPS, XRD, TG and other methods were used to characterize CEM before and after uranium adsorption.

[0057] 3. Results Analysis

[0058] 3.1 Characterization

[0059] This example measures the surface area and pore size of CEM and EM. The surface area of ​​EM is 14.7 m 2 / g, and the pore size is 19.7nm. The surface area of ​​CEM is 5.23m 2 / g, and the pore size is 19.8nm. Compared with EM, the surface area of ​​CEM is reduced and the pore size is slightly increased, which may be the reason why the complexation of CS and EM makes the structure of the hybrid material more stable. Figure 1 The SEM images of EM and CEM show that EM is a relatively regular rectangle with a slightly rough surface and micropores. After adding chitosan, CEM is a rectangle with a significantly larger volume than EM and a rough surface, but micropores can still be observed.

[0060] In the infrared spectrum of EM ( Figure 1 c), 3472cm -1 The peak at 3152 cm is the stretching vibration of phenolic hydroxyl groups. -1 The broad peak at 1722 cm is the associative stretching vibration peak of phenolic hydroxyl groups. -1 The stretching of the C=O bond of carboxylic acid is 1623 cm -1 The NH bending vibration peak is at 1589cm -1 It is the asymmetric vibration peak of COO-. 1193cm -1 is the bending vibration peak of phenolic hydroxyl group, 1064cm -1 The peak of CO vibration of CH-OH is 1035cm -1 The CO vibration peak of CH2-OH is at 687cm -1 and 574cm -1 The stretching vibration peak of Cu-O appears at 671cm -1The peak at 3472cm is the OCN peak vibration of DMF. In summary, the ellagic acid / Cu-MOFs was successfully prepared. -1 The peak at 1589cm disappears. -1 The asymmetric vibration peak of COO- at 1651cm -1 The -NC=O vibration peak was generated at 1193cm -1 The bending vibration peak of phenolic hydroxyl group is enhanced and sharpened, 1064cm -1 The CO vibration peak of CH-OH disappeared, and the stretching vibration peak of Cu-O still existed, which indicated that chitosan / copper ellagic acid-MOFs were successfully prepared and that functional groups such as hydroxyl, carboxyl and amino groups existed on the surface of CEM. Figure 1 d is the XRD spectrum of EM and CEM. In the spectrum of EM, the diffraction peaks at 8.0°, 8.6°, 12.3°, 16.0°, 19.6°, 27.2°, 28.3°, and 32.1° are 001, 110, 220, 311, 420, 731, 773, and 132, respectively. The XRD spectrum of CEM is basically consistent with that of EM.

[0061] 3.1.1TG

[0062] Figure 2 a is the thermogravimetric graph of EM. 30-220℃, the mass loss in this stage is related to the evaporation of water, acetic acid and guest molecules in EM. At 220-340℃, the framework of EM is gradually destroyed. When the temperature is 340-500℃, the ellagic acid in EM decomposes. When it exceeds 500℃, the temperature is too high, causing CEM to gradually carbonize. The final residual weight of EM is 35wt.%. Figure 2 In b, at 30-180°C, the loss of crystalline water in CEM leads to a decrease in weight, at 180-380°C, chitosan degrades and the structure of CEM is gradually destroyed. At 380-800°C, ellagic acid in CEM is pyrolyzed, and the high temperature causes the material to gradually carbonize, and the final residual weight of CEM is 40wt.%.

[0063] The stability of EM and CEM in water is as follows Figure 3As shown. EM and CEM were added to natural seawater and 10 mg / L uranium solutions with pH=6 and pH=8, respectively, and shaken at 25°C for 24 hours. It can be observed that the color of the solution remained basically unchanged when EM and CEM were first added to the seawater. After 24 hours, the color of the seawater containing EM changed significantly, and black particles precipitated at the bottom. The seawater containing CEM changed color slightly because CEM was partially suspended in the water, and the solution was more transparent. Similarly, the situation of EM and CEM in uranium solution was similar to that in seawater. The color change of the solution containing EM can be clearly observed. This may be caused by the dissolution of ellagic acid in the sample. In summary, it can be seen that after the addition of CS, the stability of the sample in aqueous solution is enhanced.

[0064] 3.2pH

[0065] Take 10mg CEM to absorb 90mL 10mg / L uranium solution. The result is as follows Figure 4 As shown in a, when the initial pH of the uranium solution is 4-6, as the pH increases, the adsorption effect of CEM on uranium gradually increases. At this time, the uranium ions in the solution are positively charged (UO2)3(OH)5 + The adsorption rate reaches the maximum when pH=6, at which time the adsorption rate of CEM to uranium can reach 99%. As the pH rises, (UO2)2CO3(OH)3 - Gradually it becomes the dominant ion in the solution. At this time, the adsorption effect of CEM on uranium gradually decreases. When pH = 8, the removal rate of CEM on uranium is 90%. When the pH exceeds 8, the uranyl ions in the solution are mainly (UO2)2(CO3)3 4- In this case, the adsorption effect of CEM on uranium is significantly reduced.

[0066] 3.3 Recycling

[0067] After 7 adsorption-desorption cycles ( Figure 4 b), the adsorption rate of CEM to uranium decreased from 99.6% to 93.3%, and the desorption rate of uranium increased from 87% to 96%, and then stabilized at around 91.5%, which shows that CEM has good recycling performance.

[0068] 3.4 Adsorption kinetics

[0069] 10 mg of CEM was taken to adsorb 90 mL of 10 mg / L uranium solution, and the adsorption amount of CEM on uranium at different reaction times was measured. The adsorption results were fitted using the pseudo-first-order kinetic model (3), pseudo-second-order kinetic model (4) and intra-particle diffusion model (5).

[0070]

[0071] Among them, q t(mg / g) is the adsorption amount of uranium by CEM at time t (min), k1, k2 and k i are the parameters of pseudo-first-order kinetic model, pseudo-second-order kinetic model and intraparticle diffusion model, respectively.

[0072] Adsorption kinetics can determine the rate of solute uptake and the residence time required to complete the adsorption reaction. Figure 5 The effect of adsorption time on the adsorption of U(VI) by CEM and EM was investigated. At 298K, 0.010g of adsorbent adsorbed 90.0ml of uranium solution with a pH of 6 and a concentration of 10.5mg / L. Figure 5 As shown in a, the adsorption of uranium by CEM reaches equilibrium in about 180 minutes. The adsorption of uranium by EM reaches equilibrium in about 420 minutes. Under the same conditions, the adsorption effect of CEM on uranium is significantly better than that of EM, and its related kinetic parameters are shown in Table 1. The results show that the adsorption kinetics of U(VI) by CEM and EM conform to the quasi-second-order model. This shows that the adsorption of U(VI) by CEM and EM is chemical adsorption. The intraparticle diffusion model of uranium adsorption by CEM and EM was studied, and the results are shown in Figure 5 b and Table 2. The adsorption process of uranium by CEM and EM includes two stages. The first stage is the process of uranium moving to the adsorbent surface and instantaneous adsorption, and the second stage is the process of diffusion within the particles and gradually reaching equilibrium. k1>k2, this is because at the initial stage of adsorption, there are enough adsorption sites on the adsorbent surface, and the adsorption rate is fast at this time. As the adsorption sites are gradually occupied, the adsorption rate decreases.

[0073] Table 1 Adsorption kinetic parameters

[0074]

[0075] Table 2 Parameters of intraparticle diffusion model for uranium adsorption by CEM and EM

[0076]

[0077] 3.5 Adsorption isotherms

[0078]

[0079]

[0080] Among them, q m (mg / g) is the maximum adsorption capacity, K L , K F and K are the isothermal adsorption constants.

[0081] like Figure 6As shown in Table 3, the adsorption capacity of CEM for uranium increases with increasing temperature. At 308K, the adsorption capacity of CEM for uranium can reach 790mg / g. The Langmuir model (6), Freundlich model (7) and Langmuir-Freundlich model (8) are used to fit the amount of uranium adsorbed by CEM at different temperatures, and the parameters are shown in Table 3. The results show that the adsorption process of uranium by CEM is more consistent with the Langmuir-Freundlich model, which indicates that the adsorption of uranium by CEM has both chemical monolayer adsorption and physical multilayer adsorption. Compared with other MOFs materials, CEM has a better adsorption effect on uranium.

[0082] Table 3 Adsorption isotherm parameters

[0083]

[0084] 3.6 Adsorption thermodynamics

[0085] Thermodynamic parameters are shown in Table 4. The adsorption amount decreases with increasing temperature (Table 4), ΔH 0 >0, indicating that the process of CEM adsorbing uranium is an endothermic reaction. ΔS 0 >0 indicates that the randomness and disorder of the solid-liquid interface increase during the adsorption process. ΔG 0 <0, which means that the adsorption process of CEM on uranium is spontaneous and thermodynamically feasible. In summary, the adsorption process of CEM on U(VI) is a spontaneous endothermic process, which is consistent with the adsorption isotherm results and Figure 6 Consistent.

[0086] Table 4 Thermodynamic parameters of adsorption

[0087]

[0088] 3.7 Selectivity

[0089] This example studies the adsorption selectivity of CEM and EM for uranium. The results show that ( Figure 7 a1, 7a2), the Kd values ​​of CEM and EM for uranium are significantly higher than those for other elements, among which the Kd value of CEM for uranium is 30.5 times that of vanadium, and the Kd value of CEM for uranium is 16.4 times that of EM for uranium. This shows that EM itself has a high adsorption selectivity for uranium, but after adding CS, the adsorption selectivity of CEM for uranium is further improved.

[0090] Effect of anions on uranium adsorption by CEM Figure 7 b, 7c. According to the actual anion concentration in seawater, the Cl - (0.1-0.8mol / L), NO3 -(0.001-0.016mol / L) pH = 6.0 10mg / L uranium solution. The results are shown in the figure. Chloride ions have a certain inhibitory effect on CEM adsorption of uranium, but in the presence of high concentrations of chloride ions, the adsorption rate only drops from 99% to 85%, and CEM still has a good adsorption effect on uranium. Nitrate ions have little effect on CEM adsorption of uranium. Therefore, CEM can be used for uranium extraction from seawater.

[0091] 3.8 Adsorption mechanism

[0092] SEM images of CEM after uranium adsorption Figure 8 a1, 8a2. After uranium adsorption, some of the cuboids in the CEM are connected together to form a sheet, but there are still some irregular cuboid structures on its surface, but their morphology is obviously narrowed and rod-shaped. After desorption 7 times, the CEM changes from a cuboid to an irregular polyhedron, and uniform and dense micropores are formed on the surface ( Figure 8 b1, 8b2). From the SEM-Mapping diagram of CEM ( Figure 8 c1~8c8), it can be seen that C, N, O, Cu, and U elements are evenly distributed on the surface of CEM-U, indicating that the CEM sample preparation is uniform and the surface functional groups are evenly distributed.

[0093] like Fig. 9 As shown, the EDS spectrum of CEM shows characteristic peaks of Cu, N, C and O, indicating the presence of organic linkers. The characteristic peak of U appears in the EDS of CEM-U after adsorption, indicating that CEM successfully adsorbs uranium. D-CEM can still detect the presence of U in the L layer, which is due to incomplete desorption.

[0094] After adsorption, an O=U=O peak (919 cm -1 ). After adsorption, 3418cm -1 The peak at 3201cm -1 A broad peak is generated at 1698 cm. The carboxyl C=O peak shifts to 1698 cm -1 , 1624cm -1 The NH peak intensity at 1475cm-1 is weakened, and the -NC=O peak disappears. -1 It is the stretching of carboxylic acid group. 1163cm -1 The COC vibration peak appears at 1038cm -1 The CH2-OH vibration disappears. When CEM adsorbs 100 mg / L uranium, the O=U=O peak intensity increases significantly. In summary, the hydroxyl, amino, and carboxyl groups on CEM participate in the adsorption of uranium. In the infrared spectrum of D-CEM after analysis, the carboxyl C=O peak shifts to 1692 cm -1 , -NC=O peak disappears, NH bending vibration disappears, at 1426cm-1 The -NH vibration peak appeared at 1372cm -1 Appearance-COO - At the same time, after desorption, the Cu-O peak shifted from 688 cm -1 and 573.6cm -1 The shift to 695 and 594.1cm -1 This indicates that the structure of CEM has changed after multiple desorptions.

[0095] Fig.10 The XPS graphs of CEM before and after uranium adsorption are shown in the figure. As shown in the figure, after adsorption, the spectrum of CEM-U has a U peak. In the U4f spectrum of CEM-U, U 4f appears at 382.2eV and 393.0eV respectively. 7 / 2 and U 4f 5 / 2 This indicates that CEM successfully adsorbed uranium, which is consistent with the results of EDS and infrared. In the C1s spectrum of CEM, 284.8eV is the CC / C=C bond, 286.2eV is the CO bond, and 288.3eV is the C=O bond, indicating that the CEM surface contains carboxyl groups. After adsorption, the CO bond shifts to 286.3eV, and the C=O bond shifts to 288.4eV, indicating that the carboxyl group participates in the reaction. In the O1s spectrum of CEM, the peak at 530.9eV is the MO bond between metal and oxygen, and the peak at 533.3eV is the C-OH peak. After adsorption of U, O2 - The peak disappears, and a new peak is generated at 531.3eV, which is the CO peak. The C-OH peak shifts to 533.4eV after adsorption, indicating that the hydroxyl groups on the CEM surface participate in the reaction. In the N1s spectrum of CEM, the peak at 399.7eV is caused by NC=O / -NH2, and the peak at 401.7eV is caused by -NH3 + After adsorption, the NC=O / -NH2 peak shifts to 400.1eV, and -NH3 + The peak shifted to 402.2 eV, indicating that the amino group participated in the adsorption of uranium. Fig.10 The third row on the right shows the Cu2p spectrum of CEM, where Cu2p 3 / 2 、Cu2p 1 / 2 Strong diffraction peaks appear at 934.4eV and 954.0eV respectively. Cu2p at 934.4eV 3 / 2 Peak corresponds to Cu 2+ The characteristic peaks at 940-945eV and 960-965eV indicate the presence of Cu(II). After uranium adsorption, all peaks shifted to higher binding energy. In summary, during the uranium adsorption process, the carboxyl, hydroxyl and amino groups on CEM participated in the reaction.

[0096] The experiment of this example shows that CEM has a higher adsorption selectivity for uranium than EM, and the Kd value of CEM for uranium is 16.4 times that of EM. Meanwhile, the stability of CEM in water is significantly stronger than that of EM.

[0097] In summary, this embodiment uses chitosan, ellagic acid and copper nitrate as raw materials to prepare chitosan-biomimetic MOFs, namely CEM, for uranium extraction from seawater. Experiments show that the adsorption of uranium by CEM is a spontaneous endothermic reaction and a chemical adsorption. And at 308K and pH = 6, the maximum adsorption capacity of CEM for uranium can reach 790mg / g. From the characterization results, it can be seen that the surface of CEM contains hydroxyl, carboxyl and amino groups, and has better stability in water than EM. CEM has good recycling performance. After 7 cycles, the removal rate of uranium of 5mg / L is maintained at more than 93%. At the same time, after adding CS, the selective adsorption effect of EM on uranium is further improved. In simulated seawater, the Kd value of CEM for uranium is 16.4 times that of EM for uranium, and it is also 30.5 times that of vanadium. In summary, CEM has a higher selective adsorption performance for uranium and has strong stability in water, so it can be used for uranium extraction from seawater.

[0098] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.

[0099] Finally, it should be emphasized that in order to allow ordinary technicians in the field to more easily understand the improvements of the present invention over the prior art, some descriptions of the present invention have been simplified, and for the sake of clarity, some other elements are omitted in this application document. Those skilled in the art should realize that these omitted elements may also constitute the content of the present invention.

Claims

1. A method for preparing a chitosan-bionic MOFs adsorbent, characterized in that: The steps include: Put ellagic acid in a container, add copper nitrate, water, glacial acetic acid and DMF, stir and heat, then cool to room temperature, add chitosan, stir at room temperature, and centrifuge to obtain a solid, which is the chitosan-bionic MOFs adsorbent.

2. The method for preparing the chitosan-bionic MOFs adsorbent according to claim 1, characterized in that: The mass ratio of ellagic acid, copper nitrate and chitosan is 6:3:

10.

3. The method for preparing the chitosan-bionic MOFs adsorbent according to claim 1, characterized in that: Every 0.3 g of ellagic acid corresponds to 0.15 g of copper nitrate, 5 mL of water, 7.5 mL of glacial acetic acid, 10 mL of DMF and 0.5 g of chitosan.

4. The method for preparing the chitosan-bionic MOFs adsorbent according to claim 1, characterized in that: The stirring and heating temperature was 120°C and the time was 1 h.

5. The method for preparing the chitosan-bionic MOFs adsorbent according to claim 1, characterized in that: The stirring time at room temperature was 0.5 h.

6. The method for preparing the chitosan-bionic MOFs adsorbent according to claim 1, characterized in that: The centrifugal speed was 6000 r / min and the time was 5 min.

7. Chitosan-bionic MOFs adsorbent, characterized by: The adsorbent is prepared by the method for preparing the chitosan-bionic MOFs adsorbent according to any one of claims 1 to 6.

8. The use of the chitosan-bionic MOFs adsorbent according to claim 7 in extracting uranium from seawater, characterized in that: The chitosan-bionic MOFs adsorbent is added into seawater to adsorb uranium in the seawater.

9. The use of the chitosan-bionic MOFs adsorbent in extracting uranium from seawater according to claim 8, characterized in that: Every 10-20 mg of chitosan-bionic MOFs adsorbent corresponds to 90-200 mL of seawater.

10. The use of the chitosan-bionic MOFs adsorbent in extracting uranium from seawater according to claim 8, characterized in that: The pH of the seawater is 6-8 and the temperature is 288-308 K.